Efecto de los compuestos bioactivos de algunos alimentos en la salud (2009)
ABSTRACT: Phytochemical substances are bioactive compounds that have special interest for scientist because of the health-promoting properties that have been demonstrated in scientific studies. Some consumers are interested to eat these products to be healthier; therefore they are requiring information about of the nutritional properties in functional foods which could be placed in the product advertising label. This review focuses on researches about bioactive compounds and the relevance of functional foods for nutrition and health, bringing an overview of what is published about bioactive compounds and the relationship between diet and health. Although these compounds are not considered essential nutrients, this article discusses the biological activity of those compounds, in particular their properties and the resulting health benefits.